Effect of Iron Applications on Fe, Zn, Cu and Mn Compositions of Grapevine Leaves - OZDEMIR, GULTEKIN; TANGOLAR, SEMIH (Asian Journal of Chemistry, 2010)
In present study, different grapevine genotypes having different resistance levels to CaCO3 were used as plant material. Genotypes were grown in pots including CaCO3 concentrations of 10, 30 and 50 %. For each medium, 4 different soil with Fe applications were performed. These are: i) 20 ppm Fe (as FeSO4) + farmyard manure (100 g/pot/5 kg soil), ii) 20 ppm Fe (as Fe-EDDHA) iii) 20 ppm Fe (as FeSO4) + citric acid (as 10 % percentage of applied FeSO4), iv) control (soil without Fe). In order to determine the effects of applications on micro element concentrations of leaves were examined. As a result of the study, Fe, Zn, Cu and Mn concentrations of all tested genotypes were decreased with increasing levels of CaCO3. Applications of Fe-EDDHA and FeSO4 + citric acid showed better results when all applications compared in respect of leaves Fe, Zn, Cu and Mn concentrations. The highest Fe, Zn, Cu and Mn concentrations were determined in Yalova incisi genotype.